“In cammino da Husserl a Heidegger”? L’arte come “ontologia indiretta” nell’ultimo Merleau-Ponty - Negri, Federica (Scenari, 2021)
The purpose of the contribution is to highlight the reasons for the comparison between the proposal of an "indirect ontology" by Merleau-Ponty and the philosophy of Heidegger, in order to discuss the affinities and divergences that emerge from the texts of the last phase of thought of the French philosopher.